Efficient Hydrogen Evolution Reaction with Bulk and Nanostructured Mitrofanovite Pt3Te4 - Gianluca D’Olimpio; Lixue Zhang; Chia-Nung Kuo; Daniel Farias; Luca Ottaviano; Chin Shan Lue; Jun Fujii; Ivana Vobornik; Amit Agarwal; Piero Torelli; Danil W. Boukhvalov; Antonio Politano (Nanomaterials, 2022)
Here, we discuss the key features of electrocatalysis with mitrofanovite (Pt3Te4), a recently discovered mineral with superb performances in hydrogen evolution reaction. Mitrofanovite is a layered topological metal with spin-polarized topological surface states with potential applications for spintronics. However, mitrofanovite is also an exceptional platform for electrocatalysis, with costs of the electrodes suppressed by 47% owing to the partial replacement of Pt with Te. Remarkably, the Tafel slope in nanostructured mitrofanovite is just 33 mV/dec, while reduced mitrofanovite has the same Tafel slope (36 mV/dec) as state-of-the-art electrodes of pure Pt. Mitrofanovite also affords surface stability and robustness to CO poisoning. Accordingly, these findings pave the way for the advent of mitrofanovite for large-scale hydrogen production.